1978
DOI: 10.1530/jrf.0.0530067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sexual stimulation on plasma levels of LH and testosterone in rams from high- and low-fertility flocks

Abstract: Plasma LH and testosterone levels did not differ significantly between high and low fertility rams before or after sexual stimulation (ejaculation or teasing). Repeated stimulation caused significant elevation of mean plasma LH and an almost significant rise in testosterone concentration. Plasma testosterone peaks followed those of LH after 30-60 min. A single sexual stimulation did not always cause an LH peak or increase the mean LH level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Sniffing, nudging, Flehmen, mounting and ejaculation are commonly involved in the male sexual courtship. Some reports have shown that sexual activity or proximity of oestrous females also increased plasma concentrations of LH and testosterone in the mouse (Coquelin & Bronson, 1980), rat (Kamel & Frankel, 1978), hamster (Macrides et al, 1974), rabbit (Agmo, 1976), monkey (Herndon et al, 1981), boar (Liptrap & Raeside, 1978), bull (Katongole et al, 1971) and ram (Sanford et al, 1974a;Moore et al, 1978). IUius et al (1976) reported that mature rams kept for 6 months in close proximity with cycling (oestrus induced) ewes had larger testes, higher testosterone concentrations and greater sexual and aggressive activity compared with those kept isolated from females.…”
Section: Introductionmentioning
confidence: 99%
“…Sniffing, nudging, Flehmen, mounting and ejaculation are commonly involved in the male sexual courtship. Some reports have shown that sexual activity or proximity of oestrous females also increased plasma concentrations of LH and testosterone in the mouse (Coquelin & Bronson, 1980), rat (Kamel & Frankel, 1978), hamster (Macrides et al, 1974), rabbit (Agmo, 1976), monkey (Herndon et al, 1981), boar (Liptrap & Raeside, 1978), bull (Katongole et al, 1971) and ram (Sanford et al, 1974a;Moore et al, 1978). IUius et al (1976) reported that mature rams kept for 6 months in close proximity with cycling (oestrus induced) ewes had larger testes, higher testosterone concentrations and greater sexual and aggressive activity compared with those kept isolated from females.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of sexual stimulation on testosterone and LH plasmatic levels has been determined in different species. The sexual stimulation caused a significantly increased mean plasma LH in bulls (Katongole et al 1971) and in rams (Moore et al 1978) immediately after ejaculation; this LH peak was followed by a peak of the testosterone concentration between 30 and 60 min after the sexual stimulation. However, the plasma concentrations of LH and testosterone did not show consistent changes up to 4 h after sexual stimulation or ejaculation in stallions (Rabb et al 1989).…”
Section: Introductionmentioning
confidence: 88%
“…The sexual stimulation caused a significantly increased mean plasma LH in bulls (Katongole et al. 1971) and in rams (Moore et al. 1978) immediately after ejaculation; this LH peak was followed by a peak of the testosterone concentration between 30 and 60 min after the sexual stimulation.…”
Section: Introductionmentioning
confidence: 95%